TEACHER AWARENESS IN IMPLEMENTING MULTILITERACY LEARNING IN PHASE C PRIMARY SCHOOLS - Widyaningrum, Heny Kusuma; Tryanasari, Dewi; Lestari, Sri; Rulviana, Vivi; Chasanatun, Fida (Universitas Labuhanbatu, 2025)
Purpose-Teacher awareness includes understanding the importance of student-centered learning. A conscious teacher will try to understand students' needs, interests, and potential. Therefore, teachers should prepare various ways to teach multiliteracy learning. This study aims to find out and analyze teachers' awareness in phase C classes regarding multiliteracy learning.Methodology—This study employed a mixed-methods approach, specifically an explanatory sequential design. In phase C, 22 elementary school teachers participated. This research used questionnaires and interviews as instruments. Data processing techniques were carried out through editing, coding, and tabulation processes.Findings-This study describes teacher awareness of multiliteracy learning from the planning, implementation, and assessment evaluation stages. In the planning stage, the average score was 3.52. This shows that teachers know students' needs and actively integrate them into learning plans. In the implementation stage, the average score was 3.79. This shows that teachers commit to multiliteracy teaching by consistently following their plans and reflecting on learning strengths and weaknesses. In the evaluation stage, the average score was 3.72. This shows that the teacher has made an assessment according to multiliteracy learning.Significance-This study is the basis for compiling a program for implementing multiliteracy activities at the elementary school level to develop student independence as creative, innovative, productive, and characterful learners. This study contributes ideas to elementary school teachers regarding the importance of teacher awareness of multiliteracy learning so that students' understanding is broader and can produce good student learning outcomes.Keywords: Teacher self-awareness, multiliteracy learning, phase C class